Comparative analysis of milk production, composition, and plasma metabolomics across various dairy goat breeds in Yunnan Province, China - Xiang, Xun; Chang, Hua; Khan, Samiullah; Khan, Ibrar Muhammad; Zhu, Feiyan; Yang, Linfu; Duan, Gang; Li, Jiming; Nassar, Nourhan; Dai, Feiyan; Mao, Huaming (Frontiers in Veterinary Science, 2025)
The present study involved crossing Alpine goats with Yunshang black bucks from Yunnan Province to produce Alpine-Yunshang dual-purpose F1 (AYF1) goats. The AYF1 goats were compared with Saanen and Toggenburg goats by evaluating milk yield, composition, and molecular markers in order to identify metabolites using liquid chromatography–mass spectrometry (LC–MS) technology. A total of 18 goats were selected, with 6 goats from each breed forming 3 groups. Daily milk yield was recorded, and milk composition was analyzed on days 60 and 120 of lactation. The results showed that on day 60, Saanen and AYF1 goats had significantly higher protein and fat contents than Toggenburg goats. On day 120, AYF1 goats had higher fat content, while Saanen goats had higher protein content compared to Toggenburg goats. There were no differences (p > 0.05) in milk yield among the breeds during the first, second, and fourth months; however, the Saanen breed yielded more milk during the third month compared to the other breeds (p < 0.05). Metabolomics analysis revealed a total of 1,108 distinct metabolites in the positive ion mode and 360 in the negative ion mode. The majority of these metabolites were found at higher levels in Saanen goats compared to other breeds. The relative abundance of 2-phenylacetamide, 5-aminolevulinic acid, and ureidopropionic acid was significantly higher in Saanen goats compared to AYF1 goats (p < 0.05). In the initial screening, 55 common and 17 useful differential metabolites were identified. A total of 17 metabolites, including 12 metabolic pathways and 7 functional classifications, were investigated using the KEGG platform. Metabolomics analysis showed that Saanen dairy goats produced higher levels of L-fucose, 4-acetamidobutanoic acid, L-tyrosine, and D-galactose, suggesting their involvement in milk production. In contrast, AYF1 goats had higher levels of sucrose, L-proline, ectoine, and biotin, suggesting their possible role in the metabolism of milk constituents. These findings offer insights into breed-specific milk metabolite profiles, highlighting the potential of AYF1 goats as a beneficial dual-purpose genotype for enhanced dairy and metabolic performance.